Mobile Networks and Management Third International ICST Conference, MONAMI 2011, Aveiro, Portugal, September 21-23, 2011, Revised Selected Papers - Pentikousis, Kostas; Aguiar, Rui L.; Sargento, Susana; Agüero, Ramón (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the Third International ICST Conference on Mobile Networks and Managements (MONAMI 2011) held in Aveiro, Portugal, in September 2011. The 30 revised full papers were carefully selected from numerous submissions and are organized thematically in 5 parts. These are mobile and wireless networks, self organized and mesh networks, new approaches for network visualization, network services, and security.